The influence of the period of collection of flows in industrial construction without using additional labor resources - Tugai, O.A.; Ivaneiko, I.D.; Dubynka, O.V.; Shebek, M. O.; Ivaneiko, M.M.; Oilynyk, V.M. (Ways to Improve Construction Efficiency, 2023)
In the non-rhythmic flow construction of industrial facilities, there are processes with a reserve of unused labor resources on works and grabs, which affect the term of work (the period of deployment of flows). The analysis of non-rhythmic works showed that they have works with a period of curtailment of flows of greater than the smallest value and they have a reserve of unused labor resources, but do not affect the terms of execution of works. It is proposed to reduce the duration of non-rhythmic flow works on technologically identical processes by using unused labor resources on works with an increased flow curtailment period on interdependent grippers. Performed preliminary studies showed that interdependent grabs for parallel work are determined by a rank matrix with priority on the OVRR front. These jobs with increased flow deployment period showed that redistributing work volumes between two jobs reduces the duration of jobs. In previous studies, the redistribution of the volume between these two works has an abstract nature without determining the technological homogeneity of the two works. The redistribution of non-rhythmic work volumes is forged in it into technologically identical types of occupations. For processes with an increased period of curtailment of flows, it is proposed to balance two jobs by a parallel method of performing work on technologically identical types of work without the use of additional labor resources. Optimizing the reduction of the construction period involves the use of parallel methods on two technologically identical works with an increased flow curtailment period. The example shows examples of balancing two jobs by using special and universal (excavator) machines with specialized specialists or complex crews. Technical and economic indicators were determined for the performed optimization.